TRENDS IN COMMUNITY AND CITIZENS’ INFORMATION SERVICES IN CANADA AND ABROAD: THE EMERGENCE OF "ONE STOP" INFORMATION ’’SUPER- MARKETS”/TENDANCES ACTUELLES DANS LES SERVICES D’INFORMATION DANS LES COMMUNAUTES DU CANADA ET LES PAYS STRANGERS: L’APPARITION - Goodman, Henry James Abraham (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2022)
see pdf